2022
DOI: 10.1088/2053-1591/aca31c
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of HA-oyster shell based on biopolymer - propolis as an agent of dental enamel remineralization material

Abstract: This study aims to make gel composites by synthesizing and characterizing hydroxyapatite (HA) from oyster shell (Crassostrea gigas) as an essential ingredient for remineralization gel in teeth. The method used to synthesize HA is the precipitation method. HA is synthesized with a variation of calcination for 8 hours at 1000°C and aging time for 24 hours to get the best result. The size of the HA crystal obtained is 14 ± 4 nm, with a degree of crystallinity of 91.54%. The result of the HA-oyster shell is used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…The biogenic materials can be derived from marine shells, such as abalone mussel shells, green mussel shells, oyster shells, and sand lobster shells, all with high levels of Ca. [15][16][17][18] This study used long-spined sea urchin (LSSU, Diadema setosum) shells from Indonesia that had never been used for HAp nanorod synthesis. The Ca content of the shells under the effect of the calcination temperature has been studied in previous research and was found to be over 93%.…”
Section: Introductionmentioning
confidence: 99%
“…The biogenic materials can be derived from marine shells, such as abalone mussel shells, green mussel shells, oyster shells, and sand lobster shells, all with high levels of Ca. [15][16][17][18] This study used long-spined sea urchin (LSSU, Diadema setosum) shells from Indonesia that had never been used for HAp nanorod synthesis. The Ca content of the shells under the effect of the calcination temperature has been studied in previous research and was found to be over 93%.…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication method was divided into two steps: (1) synthesis of CHA referring to research [16,17] using the precipitation method, and (2) fabrication of scaffolds using the freeze-drying method.…”
Section: Methodsmentioning
confidence: 99%
“…The XRD (PANanalytical Type X'Pert Pro, Japan) was used to identify the crystal structure of the samples, and its data were processed by Origin Pro 8 software and presented as a curve that displays the peaks of the diffraction results, which was achieved by Gaussian fitting at the selected peaks to attain values of the 2θ and the full width at half maximum. 26 The fitting diffraction peaks were matched with JCPDS. These data can be used to obtain the lattice parameters, crystal size, microstrain, and degree of crystallinity of the SL shells, HAp, and scaffold samples.…”
Section: Chemical Composition and Crystallography Analysismentioning
confidence: 99%